2015
DOI: 10.1051/matecconf/20152105014
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for HFQ®hot stamped aluminium structural panels

Abstract: Abstract. HFQ is a deep drawing process for alloyed aluminium sheet that can be used to produce complex-stamped forms while maintaining the high-strength of 6xxx and 7xxx alloys. By adopting a strategy to design for HFQ at the platform level, designers can reduce part count (thereby reducing cost and weight), reduce gauge (thereby reducing weight), and improve part packaging. Two simple design examples are given to assist designers in evolving traditionally formed panel designs to HFQ formed solutions. Example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Further studies have confirmed this behavior for AA7075 and AA6082 alloys (Figure 17). [87,160] The potential of the HFQ forming process is not limited to the automotive industry, [161] but has also found interest in the aerospace industry, where components of particularly complex shape are required. In other studies, [102,104] the forming temperature that would give optimum forming and mechanical behavior was investigated for wing stiffener components made from AA2060.…”
Section: Hot Forming-quenching Of Aluminum Alloysmentioning
confidence: 99%
“…Further studies have confirmed this behavior for AA7075 and AA6082 alloys (Figure 17). [87,160] The potential of the HFQ forming process is not limited to the automotive industry, [161] but has also found interest in the aerospace industry, where components of particularly complex shape are required. In other studies, [102,104] the forming temperature that would give optimum forming and mechanical behavior was investigated for wing stiffener components made from AA2060.…”
Section: Hot Forming-quenching Of Aluminum Alloysmentioning
confidence: 99%
“…To improve the formability and reduce the springback, the hot-forming–quenching integrated progress (HFQ) has been developed [ 9 , 10 ]. In this process, a solution-treated sheet is quickly transferred to the cold dies, then formed and maintained in the cold dies for high forming precision and efficient strengthening [ 11 ]. This process is significantly affected by the solution conditions, the speed of transferring and forming, and the quenching rate [ 2 , 12 ].…”
Section: Introductionmentioning
confidence: 99%